Extrusion versus diffusion: mechanisms for recovery from sodium loads in mouse CA1 pyramidal neurons. (27th May 2016) - Mondragão, Miguel A.; Schmidt, Hartmut; Kleinhans, Christian; Langer, Julia; Kafitz, Karl W.; Rose, Christine R.
Abstract : Key points: Neuronal activity causes local or global sodium signalling in neurons, depending on the pattern of synaptic activity. Recovery from global sodium loads critically relies on Na + /K + ‐ATPase and an intact energy metabolism in both somata and dendrites. For recovery from local sodium loads in dendrites, Na + /K + ‐ATPase activity is not required per se . Instead, recovery is predominately mediated by lateral diffusion, exhibiting rates that are 10‐fold higher than for global sodium signals. Recovery from local dendritic sodium increases is still efficient during short periods of energy deprivation, indicating that fast diffusion of sodium to non‐stimulated regions strongly reduces local energy requirements. Abstract: Excitatory activity is accompanied by sodium influx into neurones as a result of the opening of voltage‐ and ligand‐activated channels. Recovery from resulting sodium transients has mainly been attributed to Na + /K + ‐ATPase (NKA). Because sodium ions are highly mobile, diffusion could provide an additional pathway. We tested this in hippocampal neurones using whole‐cell patch‐clamp recordings and sodium imaging. Somatic sodium transients induced by local glutamate application recovered at a maximum rate of 8 mm min −1 (∼0.03 mm min −1 μm −2 ). Somatic sodium extrusion was accelerated at higher temperature and blocked by ouabain, emphasizing its dependence on NKA. Moreover, it was slowed down during inhibition of glycolysis by sodium fluoride (NaF). Local glutamate application to dendrites revealed a 10‐fold higher apparent dendritic sodium extrusion rate compared to somata. Recovery was almost unaltered by increased temperature, ouabain or NaF. We found that sodium diffused along primary dendrites with a diffusion coefficient of ∼330 μm²/s. During global glutamate application, impeding substantial net diffusion, apparent dendritic extrusion rates were reduced to somatic rates and also affected by NaF. Numerical simulations confirmed the essential role of NKA for the recovery of somatic, but not dendritic sodium loads. Our data show that sodium export upon global sodium increases is largely mediated by NKA and depends on an intact energy metabolism. For recovery from local dendritic sodium increases, diffusion dominates over extrusion, operating efficiently even during short periods of energy deprivation. Although sodium will eventually be extruded by the NKA, its diffusion‐based fast dissemination to non‐stimulated regions might reduce local energy requirements. Key points: Neuronal activity causes local or global sodium signalling in neurons, depending on the pattern of synaptic activity. Recovery from global sodium loads critically relies on Na + /K + ‐ATPase and an intact energy metabolism in both somata and dendrites. For recovery from local sodium loads in dendrites, Na + /K + ‐ATPase activity is not required per se . Instead, recovery is predominately mediated by lateral diffusion, exhibiting rates that are 10‐fold higher than for global sodium signals. Recovery from local dendritic sodium increases is still efficient during short periods of energy deprivation, indicating that fast diffusion of sodium to non‐stimulated regions strongly reduces local energy requirements.